Kewenangan Mahkamah Konstitusi Menangani Perkara Pengaduan Konstitusional Melalui Penafsiran Konstitusi - Idris, Munawara; Bachri, Syamsul; Naswar (Alauddin Law Development Journal (ALDEV), 2023)
Constitutional complaints aim to improve checks and build a good and clean government. The Constitutional Court often rejects constitutional complaints that come in on the basis of a lack of authority. However, the Constitutional Court sometimes accepts constitutional lawsuits and even grants these requests using interpretation according to the power of The Sole Interpreter of the Constitution. Therefore, the problem raised is how the interpretation is carried out by the Constitutional Court so that it can accept a constitutional lawsuit without making changes to the constitution. This study uses normative research methods with statutory, conceptual, historical, and comparative approaches. The results of this research show that through the Judicial Review window, the Constitutional Court can resolve cases of constitutional complaints using the interpretation of indicator analogies. Because the Constitutional Court may not reject a case submitted to it on the basis of the Ius Curia Novit principle.